Intersectoral collaboration for supporting the health and wellbeing of Aboriginal families and children in out-of-home care: perspectives from Western Australian Aboriginal Community Controlled Health Organisations - Moodie, Sasha; Jones, Jocelyn; Chenhall, Richard; Williams, Robyn; Garlett, Cathy; Gibberd, Alison; O’Donnell, Melissa; McAullay, Dan; McNamara, Bridgette; Eades, Sandra (Frontiers in Public Health, 2024)
Western Australia has one of the highest rates of Aboriginal children entering out-ofhome care in Australia. Kinship care is the preferred culturally safe out-of-home care option for Aboriginal children, yet all jurisdictions, including Western Australia, are far from meeting bestpractice national standards. Intersectoral collaboration is a key primary healthcare principle and internationally recognised for improving health systems and outcomes. This paper presents findings from a qualitative research project investigating Aboriginal primary healthcare workers' experiences of intersectoral collaboration challenges and strengthening opportunities.Methods: Constructivist grounded theory guided this research involving 55 semi-structured interviews and four focus group discussions with Aboriginal primary healthcare workers. The research was guided by Indigenous methodologies and led by Indigenous researchers Participants were recruited from seven Aboriginal Community Controlled Health Organisations located across Perth metro, Pilbara, Midwest/Gascoyne and Southwest regions in Western Australia.Results: Key themes identified around intersectoral collaboration challenges were communication, including information sharing and interagency meetings, and the relationship with the government sector, including trust and the importance of the perception of Aboriginal health service independence. Key themes around strengthening areas to improve intersectoral collaboration included strengthening service resourcing and coverage, including the availability of services, and addressing high program turnover. The need for a shift in approach, including more emphasis on Aboriginal-led care and aligning approaches between sectors, was another area for strengthening.Discussion: This study addresses a significant research gap concerning out-of-home care, kinship care, and intersectoral collaboration in an Australian Aboriginal context. Findings highlighted the need to review the out-of-home and kinship models of care to strengthen the system, including creating more formal and structured modes of collaborating and better resourcing family support and kinship care.